Antibacterial Activities of Perfume: Combination Flower Magnolia alba, Cananga odorata and Mimusops elengi L, Fixed with Pogostemon cablin Oil - Nasution, Rosnani; Azwar, Azalia Izdhihar; Helwati, Hira; Marianne (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Abstract: The making of perfume from the combination Magnolia alba (M. alba) flower oil, Cananga odorata (C. odorata) and Mimusops elengi L (M. elengi) fixed with Pogostemon cablin oil (P. cablin) have been done. Essential oil of M. alba and C. odorata was distilled by water distillation and extraction essential oil of M. elengi flower using n-hexane evaporated solvent method. Composition perfume through organoleptic test obtained with a ratio of 4% v/v, 4% v/v, and 2% v/v for each essential oil M. alba, C. odorata and M. elengi. Antibacterial activity of the perfume and each of the volatile oil was performed by the disc diffusion method. Antibacterial activity test showed that perfumes were able to inhibit the growth of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) bacteria, but less active. Antibacterial activity of the perfume was more active against E. coli with an inhibitory zone of 8.3 mm and 39.81% inhibitory power than S. aureus bacterial 7.3 mm inhibition zone with 37.55% inhibitory power. Perfumes after storage for one, and two months had better antibacterial activity than before storage with an average inhibitory zone of 11-15 mm and inhibitory power of 50- 68,18%. Keywords: Antibacterial, E. Coli, C. Odorata, M. alba, M. elengi, P. cablin, , S. aureus